2016
DOI: 10.1155/2016/5380792
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Selective Inflammatory Markers in Psoriatic Patients

Abstract: The presented article studies the role of selected inflammatory and anti-inflammatory serum markers of psoriatic patients in the pathogenesis of metabolic syndrome (MS) and psoriasis. The study is based on the comparison between the group of psoriatic patients (74) and the control group (65). We found significantly higher BMI (p < 0.05) and diastolic blood pressure (p < 0.05) in the psoriatic patients. The values of waist circumference and BMI were significantly higher (p < 0.05) in the male patients compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 60 publications
2
33
0
Order By: Relevance
“…Patients with psoriasis have high levels of inflammatory markers, with C-reactive protein (CRP) (13), leptin (14) and TNF serum concentrations being significantly higher than in controls, whilst adiponectin levels are lower (14). While previous studies have separately shown an increased prevalence of CMDs (1), adipokine dysregulation (15) and increased visceral fat in psoriasis (16), to date no studies have assessed these relationships in a single cohort.…”
mentioning
confidence: 99%
“…Patients with psoriasis have high levels of inflammatory markers, with C-reactive protein (CRP) (13), leptin (14) and TNF serum concentrations being significantly higher than in controls, whilst adiponectin levels are lower (14). While previous studies have separately shown an increased prevalence of CMDs (1), adipokine dysregulation (15) and increased visceral fat in psoriasis (16), to date no studies have assessed these relationships in a single cohort.…”
mentioning
confidence: 99%
“…Recently, it has been recognized that fat cells exhibit remarkable intrinsic inflammatory properties. Adipocytes activate multiple inflammatory signaling cascades, inducing and secreting a large number of potent inflammatory cytokines such as interleukin (IL)‐6, IL‐1 and tumor necrosis factor (TNF)‐α . This weak but chronic production of pro‐inflammatory factors affect both the innate and the acquired immune system and may play a central role in the pathogenesis of psoriasis .…”
Section: Discussionmentioning
confidence: 99%
“…Adipocytes activate multiple inflammatory signaling cascades, inducing and secreting a large number of potent inflammatory cytokines such as interleukin (IL)-6, IL-1 and tumor necrosis factor (TNF)a. 5,8,9 This weak but chronic production of pro-inflammatory factors affect both the innate and the acquired immune system 10 and may play a central role in the pathogenesis of psoriasis. 11 In addition, changes in the levels of leptin, adiponectin and resistin secreted by adipocytes suggest that these factors also play an important role in the onset of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, numerous studies have shown a positive association between metabolic syndrome and adult psoriasis . However, limited studies have been done on the association between metabolic syndrome and pediatric psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…1 Recently, numerous studies have shown a positive association between metabolic syndrome and adult psoriasis. [3][4][5][6][7][8] However, limited studies have been done on the association between metabolic syndrome and pediatric psoriasis. A metaanalysis of seven studies, which assessed the metabolic syndrome and cardiovascular risks of pediatric psoriasis, found that children with psoriasis had 6.10 times the risk of having metabolic syndrome than children without psoriasis (in only three studies).…”
Section: Introductionmentioning
confidence: 99%